2012
DOI: 10.5114/aoms.2012.28563
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in women with hirsutism

Abstract: IntroductionThere are still not enough data showing whether patients with idiopathic hirsutism (IH) also have insulin resistance. The association between polycystic ovary syndrome (PCOS) and insulin resistance is well documented in the literature, but the Rotterdam Consensus has concluded that principally obese women with PCOS should be screened for the metabolic syndrome. We intended to investigate the presence/absence of insulin resistance in non-obese women with hirsutism.Material and methodsTwenty-eight wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Furthermore, Paoletti et al [19] documented that antiandrogen treatment improved hyper insulinemia in 11 women with IH. In agreement with our findings, Cebeci et al found no difference in insulin levels and HOMA between 11 nonobese women with IH and their controls [16]. Apart from the different diagnostic criteria for IH and IR used, these discrepancies could be attributed to genetic factors, lifestyle characteristics, and dietary habits.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, Paoletti et al [19] documented that antiandrogen treatment improved hyper insulinemia in 11 women with IH. In agreement with our findings, Cebeci et al found no difference in insulin levels and HOMA between 11 nonobese women with IH and their controls [16]. Apart from the different diagnostic criteria for IH and IR used, these discrepancies could be attributed to genetic factors, lifestyle characteristics, and dietary habits.…”
Section: Discussionsupporting
confidence: 87%
“…It is not clear whether the peripheral increase of androgen activity in IH affects insulin metabolism [16][17][18] and, as a result, women with IH exhibit insulin resistance. There are limited number of studies with small sample size that report an increase in insulin resistance (IR) among women with IH [17,19,20]; however, the impact of IH on metabolic syndrome (MetS) has not been documented.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Cebeci concluded that insulin level and insulin-resistant state of women with HI and control groups did not show any differences. This might be due to the small number of women with HI [28]. …”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is considered to be primarily a functional disorder of the ovary and many theories and mechanisms have been put forward on its causes to date [1]. The most popular theory of the pathophysiology of PCOS is insulin resistance [2]. Great progress has been made in this regard by molecular and clinical studies, but some questions still need answers.…”
Section: Introductionmentioning
confidence: 99%